Molecular detection of Aspergillus in samples collected from patients with suspicion of respiratory fungal infection - Oliveira, Mariana (2021)
The aim of this study was to determine the potential of the real-time multiplex PCR to detect Aspergillus spp. DNA in respiratory samples from a cohort of patients with suspicion of respiratory fungal infection. This is of particular importance in patients who are HIV positive and frequently misdiagnosed with pulmonary tuberculosis, when they suffer from aspergillosis. In this study, we have tested patients with a higher risk to develop chronic pulmonary aspergillosis (CPA): HIV+ patients as well as patients with active tuberculosis or with a previous Mycobacterium infection.